Digital Literacy: Implementasi Pelatihan English Speaking Performance pada Santriwati Pondok Pesantren Sahlan Rosyidi - Testiana Deni Wijayatiningsih; Dodi Mulyadi; Muhimatul Ifadah; Riana Eka Budiastuti; Siti Aimah; Anjar Setiawan; Betta Rizq Maulidya (Jurnal Surya Masyarakat, 2021)
The learning process and life activities during the Covid-19 pandemic proceed through online social media, so there is a need for technological literacy. This activity also happened at the Pondok Pesantren Putri Sahlan Rosyidi Semarang where the academic abilities of the female students, especially the English language, were very diverse but there was still a lack of English-speaking practice programs that were integrated with digital literacy. Initial findings of the daily English-speaking ability of female students had an average of 65 which had to be improved again. Based on this statement, our team focuses on the implementation and training of Digital Literacy through the practice of speaking English for female students at the Pondok Pesantren Putri Sahlan Rosyidi Semarang, consisting 60 female students. The method used is descriptive quantitative by applying brainstorming, group discussion, explanation, speaking practices, digital platform, and evaluation of students' digital understanding of literacy. The results show that the implementation of the practice of speaking English based on digital literacy with an increase in the average speaking English rising to 81. In addition, the female students gave a positive response to the implementation of digital literacy and the practice of speaking that was trained. They were also motivated to practice conversation or monologue by utilizing digital technology.